Makna Aksiologi dalam Manajemen Pendidikan Islam untuk Pengembangan Kualitas Pendidikan - Arif Rahman Hakim; Adang Hambali (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
Islamic education management not only focuses on administration and resource management but also integrates Islamic moral values and ethics to shape students' character. Axiology, which studies values, becomes key in determining educational goals that encompass intellectual intelligence and the formation of noble character. Therefore, understanding the meaning of axiology in Islamic education management is crucial for improving educational quality. This study aims to explore the application of axiology in Islamic education management and its impact on the quality of education. The approach used is qualitative with an in-depth literature review, analyzing expert views on axiology, educational management, and the quality of education. The research findings show that the integration of Islamic values into the curriculum, teaching, and assessment provides a strong moral foundation in education. Axiology not only supports academic achievement but also aids in character formation that aligns with Islamic teachings. Thus, the application of axiology in Islamic education management plays an important role in creating more holistic, relevant, and beneficial education for the community, both intellectually and morally for students.